Racial and ethnic differences in patterns of use and discontinuation of long-acting injectable antipsychotics using Medicaid claims data - Caballero Joshua PharmD, BCPP, FCCP; Xu Jianing MS; Hall Daniel B. PhD; Chen Xianyan PhD; Young Henry N. PhD (Mental Health Clinician, 2023)
Introduction In general, racial and ethnic differences exist in antipsychotic prescription practices. However, little is known about such differences between individual long-acting injectable (LAI) antipsychotic formulations, specifically. This study's primary objective was to determine racial and ethnic differences among LAI antipsychotic use. Secondary objectives were to identify if discontinuation rates differed between agents and by race or ethnicity. Methods International Classification of Diseases, 10th edition (ICD-10) codes were used to identify patients with schizophrenia and related disorders (18-64 years) who received an LAI antipsychotic between 2016 and 2020 using Merative Multi-State Medicaid databases. Using National Drug Code numbers for LAI antipsychotics, pharmacy claims were identified and data analyzed. Cochran-Mantel-Haenszel tests and odds ratio estimators were used to investigate conditional association between race or ethnicity and medication, while controlling for age, sex, health plan, and prescription year. Kaplan-Meier survival curves were examined, and stratified log-rank tests were conducted to compare the time until discontinuation distributions by race or ethnicity. Results The analysis included 37?712 patients. Blacks received an LAI first-generation antipsychotic more often than Whites (OR: 1.64, 95% CI: [1.56, 1.73], Hispanics (OR: 1.46, 95% CI: [1.21, 1.75]) and others (OR: 1.44, 95% CI: [1.20, 1.73]). Aside from fluphenazine decanoate showing earlier discontinuation rates for Whites over Blacks (P = .02), no significant differences in discontinuation across race or ethnicity were identified. Discussion Despite no significant differences in second-generation antipsychotic LAI discontinuation rates between Blacks and other racial or ethnic groups, Blacks received second-generation antipsychotic LAIs significantly less often than other groups. Further studies are needed to determine why differences may be occurring.